Cluster Based Certificate Revocation of Attacker’s Nodes in MANET - E.K. Neena; C. Balakrishnan (International Journal of Computer Sciences and Engineering, 2014)
Mobile ad hoc network (MANET) is a type of wireless ad hoc network. MANETs are very popular because of its infrastructure less network. Security is a major concern to provide protection between mobile nodes in hostile environment. Certificate revocation is one of the security components in mobile ad hoc networks (MANETs). Certificate revocation scheme, outperforms other techniques in terms of being able to quickly revoke attackers certificates and recover falsely accused certificates. The dynamic and wireless nature of mobile ad hoc network makes them more susceptible to many kinds of malicious attacks. Certificate revocation isolates the attackers from further participating in network activities. Certificates are issued and revoked by trusted party known as Certificate Authority. Certificate revocation invalidates the attackerï¿½s certificate which is essential in keeping the network more secured. Sometimes malicious node will try to remove legitimate nodes from the network by falsely accusing them as attackers. Therefore, the issue of false accusation must be taken into account in designing certificate revocation mechanisms. Clustering approach is able to quickly revoke certificates of accused nodes and also to explicitly distinguish false accusations. Here Warned nodes will also be involved in certificate revocation to make the scheme more efficient and reliable. Cluster based routing protocol is used for revocation of certificates that provides more security in mobile ad hoc network.